2021
DOI: 10.3389/fcimb.2021.728929
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatilla chinensis Saponins Ameliorate Inflammation and DSS-Induced Ulcerative Colitis in Rats by Regulating the Composition and Diversity of Intestinal Flora

Abstract: Pulsatilla chinensis (Bunge) Regel is a commonly used Chinese medicine for clearing away heat and detoxification, cooling blood, stopping dysentery, and anti-inflammatory effects. Pulsatilla chinensis saponins (PRS) have been identified to be responsible for producing these pharmacological activities. Studies have shown that Pulsatilla decoction has a good therapeutic effect on ulcerative colitis (UC), however, the therapeutic effect of PRS on UC has not been reported. Therefore, the purpose of this study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 34 publications
2
42
0
Order By: Relevance
“…Changes in intestinal microbiota were thought to be involved in the occurrence, development, and treatment of diseases [ 5 ]. To determine whether the intestinal microbiota of rats changed after treatment, 16S rRNA gene sequencing analysis was performed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Changes in intestinal microbiota were thought to be involved in the occurrence, development, and treatment of diseases [ 5 ]. To determine whether the intestinal microbiota of rats changed after treatment, 16S rRNA gene sequencing analysis was performed.…”
Section: Resultsmentioning
confidence: 99%
“…Alpha diversity contains four indices ACE, Chao1, Shannon, and Simpson, which is an analysis of species diversity in a single sample. ACE and Chao1 reflect the community richness of species, while Shannon and Simpson represent microbial diversity [ 5 ]. As listed in Table 1 , there were no significant differences in ACE and Chao 1 between the three MGM-DM groups and the corresponding treatment groups ( p > 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular docking showed that the protein encoded by the HSP90AA1 gene bound to aureusidin, the bioactive compound of P. chinensis , which had various anti-inflammatory effects on inflammation-related diseases ( Ren et al, 2020 ; Yang et al, 2020 ; Yang et al, 2021 ). Moreover, anemoside B4, a triterpenoid saponin extracted from P. chinensis , had also been found to ameliorate inflammation by regulating intestinal flora ( Liu et al, 2021b ) and pathways associated with NF-ÎșB and MAPK ( Ma et al, 2020 ; Zhang et al, 2021 ). In addition, dihydroberberine from P. chinense , as well as C. chinensis , was shown to alleviate ulcerative colitis by regulating the gut barrier function and immune-inflammatory response ( Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%